The provision of public services in Europe : between state, local government and market - Wollmann, Hellmut, 1936-; Marcou, Gérard, 1947- (Edward Elgar, 2010)
"The book is the first of its kind to provide a comparative analysis of the provision of social and public services in France, Italy, Germany, the UK and Norway. -- This volume, co-authored by leading national experts, topically examines whether, when, how and why the delivery of social and public services, which was historically a responsibility of local authorities, has been significantly shifted to marketized and commodified forms. However, despite this considerable change, there have been recent indications of remunicipalization in some sectors. Combining both cross-country and cross-policy comparisons in a broad range of pertinent service fields, this volume fills a noticeable gap in the international literature currently available. -- Mirroring the underlying interdisciplinary approach of the book, the findings will be useful and attractive to students of law and economics as well as political science and sociology. Academic researchers and politicians on all intergovernmental levels will also find this book insightful and stimulating."
Keywords: veřejné služby -- Evropa; sociální služby -- Evropa; sociální politika -- Evropa; veřejná správa -- Evropa; místní správa -- Evropa; public utilities -- Europe; social service -- Europe; social policy -- Europe; public administration -- Europe; local government -- Europe; srovnávací studie; comparative studies